A Letter to the Editor: Comment, Reply, and Etiquette - Donovan, Stephen K. (Journal of Scholarly Publishing, 2016)
Comments and replies (Letters to the Editor) are short notes arising from a published paper. They can be contentious, even hostile. However, comments may correct an original error or reveal alternative interpretations, support a new contribution or extend its discussion. Comments and replies can add to academic discourse, but they may tread the edges of academic civility. In these days of publication metrics, a cynical author may just use them to improve their citation statistics.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEzOC9qc3AuNDcuMi4yMTM